Investigation of potential serum biomarkers for the diagnosis of chronic back pain in horses - Mayaki, Abubakar Musa; Abdul Razak, Intan-Shameha; Mohd Adzahan, Noraniza; Mazlan, Mazlina; Abdullah, Rasedee (Saints Cyril and Methodius University of Skopje, 2023)
Back pain is one of the most common triggers of performance failure in athletic and riding horses. Diagnosis of equine back pain has been very challenging for equine practitioners, particularly in chronic cases. Therefore, the identification of blood biomarkers would facilitate the clinical differentiation of chronic back pain. This study aimed to investigate serum biomarkers of glial cell activation, axonal damage, and inflammation for the diagnosis of equine chronic back pain. Serum samples from forty horses comprising chronic back pain (CBP), back pain concurrent with lameness (BPL), lameness (LN), and healthy control (HC) (n=10 per group) were screened for ionized calcium-binding adaptor molecule 1 (Iba-1), glial fibrillary acidic protein (GFAP), phosphorylated neurofilament-H (pNF-H) by ELISA, and proinflammatory cytokines (IL-1β, IL-6, and TNF-α) by multiplex assay. Serum concentrations of GFAP (3.81±1.72 ng/mL) and pNF-H (0.76±0.18 ng/mL) were significantly (p<0.05) higher in horses with CBP when compared with other groups. Iba-1 was not significantly higher in CBP horses. There was no significant difference between the pro-inflammatory cytokines among the groups. The levels of IL-1β, IL-6, and TNF-α were also increased in the CBP than the HC control horses but lower in relation to BPL and LN horses. In addition, serum Iba-1, GFAP, and pNF-H showed a high discriminatory capacity for horses with CBP with high sensitivity (50-100%) and specificity (70-100%). This study provides evidence that serum levels of the GFAP and pNF-H may be useful in the clinical differentiation of horses with chronic back pain.